2003
DOI: 10.1128/aem.69.7.4067-4075.2003
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Atmospheric CO and Hydrogen Uptake to Microbial Dynamics on Recent Hawaiian Volcanic Deposits

Abstract: A series of sites were established on Hawaiian volcanic deposits ranging from about 18 to 300 years old. Three sites occurred in areas that supported tropical rain forests; the remaining sites were in areas that supported little or no plant growth. Sites >26 years old consumed atmospheric CO and hydrogen at rates ranging from about 0.2 to 5 mg of CO m ؊2 day ؊1 and 0.1 to 4 mg of H 2 m ؊2 day ؊1 , respectively. Respiration, measured as CO 2 production, for a subset of the sites ranged from about 40 to >1,400 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
155
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 46 publications
10
155
0
Order By: Relevance
“…We show, for example, that H 2 uptake activation energies for Bare cinders and Canopy material (82.9 kJ mol À1 and 50.8 kJ mol À1 , respectively; Figure 2) fall within ranges reported for bacterial activity (about 50-140 kJ mol À1 ), and markedly exceed values for exoenzymatic activity (10-30 kJ mol À1 ; Schuler and Conrad, 1991). This is consistent with the outcome of a previous inhibitor study (King, 2003a), which demonstrated that H 2 uptake was largely bacterial rather than exoenzymatic (Conrad, 1996). Thus, the relative importance of bacteria versus exoenzymes as a H 2 sink does not appear to be greatly affected by vegetation due to ecosystem succession, at least over the short term (that is, decades).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…We show, for example, that H 2 uptake activation energies for Bare cinders and Canopy material (82.9 kJ mol À1 and 50.8 kJ mol À1 , respectively; Figure 2) fall within ranges reported for bacterial activity (about 50-140 kJ mol À1 ), and markedly exceed values for exoenzymatic activity (10-30 kJ mol À1 ; Schuler and Conrad, 1991). This is consistent with the outcome of a previous inhibitor study (King, 2003a), which demonstrated that H 2 uptake was largely bacterial rather than exoenzymatic (Conrad, 1996). Thus, the relative importance of bacteria versus exoenzymes as a H 2 sink does not appear to be greatly affected by vegetation due to ecosystem succession, at least over the short term (that is, decades).…”
Section: Discussionsupporting
confidence: 79%
“…Canopy site surface material is characterized by an organic-rich peat-like material, while Bare site material consists of organic-poor cinders approximately 1 cm in diameter. Numerous details of this system have been described previously (King, 2003a;King and Weber, 2008;Weber and King, 2009). Temperature regimes for Bare and Canopy sites differ significantly.…”
Section: Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations